Pelaksanaan Sistem Pengolahan Data Administrasi Kependudukan di Kantor Desa Loka Jaya - Sari, Nurmaya; Zubaidah , Siti; Yuniarti, Yuniarti; Waliah, Siti; Hermansyah, Hermansyah (Journal of Administration, Governance, and Political Issues, 2025)
The implementation of the population administration data processing system at the Loka Jaya Village Office is an essential part of efforts to improve the efficiency and accuracy of population data management at the village level. This system aims to streamline the process of recording, updating, and managing population data needed for various public services, including social assistance, education, and healthcare programs. This study analyzes the implementation of the system at the Loka Jaya Village Office, focusing on its effectiveness, the challenges faced, and its impact on public service delivery. The research method employed is a descriptive qualitative approach, with data collection through interviews, observations, and documentation. The results show that although the population administration data processing system has had a positive impact on time efficiency and data error reduction, several challenges remain, particularly related to the limited human resources and existing technological infrastructure. Additionally, further training for staff is needed to maximize the potential of the system. Overall, the implementation of this system has made a significant contribution to improving the quality of public services in Loka Jaya Village.